CONSTRUCTION OF THE CENTER-VALUED QUASITRACES ON A FINITE REAL AW*-ALGEBRAS - Rakhmonova Nilufarkhon (University Research Base, 2024)
In this thesis real AW*-algebras are considered. It is proved the existence and uniqueness of the centervalued quasitrace on finite real AW*-algebras in analog to the center-valued trace on finite real von Neumann algebras.